PESANTREN AS A FORM OF SOCIAL REHABILITATION FOR NARCOTICS INSTITUTIONS OF NARCOTICS INSTITUTIONS OF CLASS II A JAKARTA - VIVI SYLVIANI BIAFRI (Polteknik Ilmu Pemasyarakatan, 2019)
Drug convicts are scattered in all prisons in Indonesia. Only some are placed in special narcotics prisons. Therefore, in accordance with SMR 58 and 59, the prison must carry out their recovery. Narcotics special prisons have the responsibility for implementing rehabilitation for narcotics convicts. This is done to prepare them to return to the midst of society and not use narcotics anymore. This research raises the problem of how the implementation of Islamic boarding schools as a form of social rehabilitation for narcotics inmates at the Class II A Narcotics Prison, Jakarta? This study aims to determine the implementation of pesantren activities as a form of social rehabilitation for narcotics convicts. This research was conducted at the Class II A Narcotics Prison, Jakarta. This study uses a qualitative research approach. This research was conducted in October 2018. The data were collected using observation, interview and document study techniques which were then processed and analyzed qualitatively. The results of this study indicate that Islamic boarding school activities as a form of social rehabilitation for narcotics prisoners have not been optimal.